A new normal in primary care: the rapid normalization of a major eHealth program in public health centers - Karl Maack; Nanna Gillberg; Ewa Wikström (BMC, 2024)
Abstract Background This study aimed to contribute to a better understanding of the context, mechanisms and outcomes in the implementation process of an eHealth video consultation program in primary care. The study focused on how the program is normalized in the primary care setting. The primary research question for this study is "in what ways is the implementation of video consultation normalized in primary care?". Methods The qualitative design and content analysis of primary data from the transcripts were based on in-depth interviews, complemented with free-text answers to open-ended survey questions and various documents. The study focuses on the large-scale implementation of the public eHealth program Närhälsan Online, which represents more than 100 health centers in Sweden's largest region of Västra Götaland. Multiagent perspectives on how the program is normalized were drawn from expressed perceptions by professions directly linked to both strategic and functional implementation, as well as administration and clinical operation. Results This study both confirms and enhances the field with a theoretical contribution in six ways to the reviewed previous research, as well as showing practical implications. It also provides multi-agent perspectives on the rapid normalization of the implementation program studied. Conclusions In relation to the rapid progression of different initiatives in eHealth, this study contributes to perspectives on specific challenges as expressed by professions directly linked to both strategic and functional implementation as well as administration and clinical operation.